2004
DOI: 10.1002/maco.200303773
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the mode of introduction of a reactive element on the high temperature oxidation behavior of an alumina‐forming alloy. Part II: Cyclic oxidation tests

Abstract: Several routes of yttrium introduction were applied to test the high temperature oxidation performance of a FeCrAl alloy. Isothermal oxidation tests were described in a previous paper (Part I of this paper in this journal, 2004, 55, 352). Cyclic oxidation tests were performed in air under atmospheric pressure on blank specimens, Y2O3 sol‐gel coated‐, Y2O3 metal‐organic chemical vapor deposited (MOCVD)‐, yttrium ion implanted‐alloys, as well as on a steel containing 0.1 wt. % of yttrium as an alloying element. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…This is particularly true for reactive-element addition, whose effect on the high-temperature corrosion of alumina-forming materials was largely studied [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true for reactive-element addition, whose effect on the high-temperature corrosion of alumina-forming materials was largely studied [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…5 shows that YAlO 3 and Y 3 Al 5 O 12 form simultaneously. After 48 h YAlO 3 is totally transformed into Y 3 Al 5 O 12 according to equation (2). The oxygen isotope distribution determined by SNMS (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies showed that the introduction of yttrium, as an oxide or as implanted ions, into the surface of a model Fe-20Cr-5Al steel did not improve the high temperature oxidation rate, nor the alumina scale adherence [1,2]. The oxidation behaviour of the so-treated alloys was compared to the oxidation behaviour of the bare steel.…”
Section: Introductionmentioning
confidence: 99%
“…Polished-cross sections were prepared and observed by optical microscopy in order to estimate the metal consumption. Samples were weighed before and after exposure to Ar/Cl 2 atmosphere; gross and net weight gains were collected in order to verify the adherence of the corrosion products to the underlying substrates [37]. The gross weight corresponds to the weight of the corroded samples together with the alumina crucible (and the spalled particles) minus the original weight of the crucible.…”
Section: Methodsmentioning
confidence: 99%